2006
DOI: 10.1002/jrs.1644
|View full text |Cite
|
Sign up to set email alerts
|

IR, Raman and SERS spectra of 5‐sulphosalicylic acid dihydrate

Abstract: IR, Raman and surface-enhanced Raman scattering (SERS) spectra of 5-sulphosalicylic acid were recorded and analysed. The vibrational wavenumbers were computed by density functional theoretical (DFT) method using B3LYP/6-31G * basis. The bands due to the stretching modes C O, C-S and SO 2 are intense in the SERS spectrum. The C-H stretching mode also appears in the SERS spectrum. The molecule is found to adsorb through both the carboxyl and sulphonyl groups. A possible tilted orientation of the molecule is sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 31 publications
0
11
0
1
Order By: Relevance
“…11. At pH 2, the spectrum consists in several bands which have been assigned following previous works by Varghese et al (2007) and Jiang et al (2002) as shown in Table 5. From pH 2 to 5, some differences can be seen: bands around 1200 cm -1 decrease, bands at 1270 and 1306 cm -1…”
Section: Spectral Characterization Of 5-ssa In Solutionmentioning
confidence: 99%
“…11. At pH 2, the spectrum consists in several bands which have been assigned following previous works by Varghese et al (2007) and Jiang et al (2002) as shown in Table 5. From pH 2 to 5, some differences can be seen: bands around 1200 cm -1 decrease, bands at 1270 and 1306 cm -1…”
Section: Spectral Characterization Of 5-ssa In Solutionmentioning
confidence: 99%
“…The characteristics bands observed at 592 and 667 cm −1 are attributed to out‐of‐plane bending of SSA ring and in‐plane bending and/or out‐of‐plane bending of SSA ring, respectively. The distinctive bands at 804 and 883 cm −1 , corresponding to γ C–H vibration of SSA ring and ∼1025 cm −1 , attributed to symmetric stretching of SO 3 group, confirm that PANI‐SSA samples are doped with 5‐sulfosalicylate anions . Further the characteristic band observed at 1666–1678 cm −1 signifies the C=O stretching of COOH confirming the presence of SSA as dopant in PANI.…”
Section: Resultsmentioning
confidence: 55%
“…In addition, SERS was employed to determine the orientation of molecules on a metal surfaces. Such fundamental molecular structure studies were carried out for: 3,5-pyrazoledicarboxylic acid and its Ce(III) and Nd(III) complexes, 94 the bis(perfluoroethanesulfonyl)imide anion (BETI , 95 5-aminoorotic acid and its new lanthanide(III) complexes, 96 5-sulphosalicylic acid dihydrate, 97 3,5-dinitrosalicylic acid, 98 self-assembly complexes of bis(pyrrol-2-ylmethyleneamine) ligands linked by alkyl spacers with Cu(II) 99 thymine, uracil and their isotopomers, 100 the nonlinear optical chromophore p-bromoacetanilide, 101 1,3-disilabutane (SiH 3 CH 2 SiH 2 CH 3 , 102 dihaloheptasilanes X 2 Si[SiMe(SiMe 3 2 ] 2 with X = F, Cl, Br, 103 5-bromouracil, 104 uracilyl-pyridinium mesomeric betaine, 105 flucytosine, 106 the food additivesˇ-hydroxy-ˇ-methylobutanoic acid (HMB), L-carnitine, and N-methylglycocyamine (creatine), 107 clioquinol and its Cu(II) complex, 108 4-mercaptopyridine aqueous solution and 4-mercaptopyridine/Ag complex system. 109…”
Section: Vibrational Studies In Chemistry Combined Raman Infrared Smentioning
confidence: 99%